Green Banking, Kesehatan Bank dan Profitabilitas dengan Corporate Social Responsibility sebagai Variabel Moderasi - Kweeswara, Corinna Octavia; Irawan, Judith Felicia Pattiwael (E-Jurnal Akuntansi; Vol 33 No 4 (2023), 2023)
The 2020 - 2021 pandemic has had an impact on banking activities. The aim of the study was to find out green banking practices carried out by the core capital bank group (KBMI) 3 during the pandemic, including CSR, as well as the health conditions of the banks. The study is based on the theory of Socially Responsible Investment and the concept of bank soundness. The study sample is KBMI 3 banks listed on the IDX. The operational variable is the dependent variable ROA as a measure of profitability. Meanwhile, the independent variables are CAR, BOPO, and NPL as bank health variables, 16 Green Banking indicators and 91 CSR indicators. The data analysis technique uses multiple and simple linear regression methods. The results show that the BOPO variable has a negative effect on bank profitability. Meanwhile, other variables have no effect. Thus, the study results provide findings that during a pandemic, KBMI 3 banks focused on maintaining cost efficiency, one measure of bank health. The research results are in line with the concept of bank soundness. The research contribution is that in the conditions of Covid-19, the KBMI 3 bank supports sustainability but maintains more cost efficiency. Keywords: Green Banking, Corporate Social Responsibility, Specific Condition, Cost Efficiency.